Modernization of Government Governance in China - Shen, Ronghua. author. aut Link
XXIII, 287 p. 11 illus.
Keywords: This book provides an all-round analysis and exploration of the course, status quo and future of the Chinese Government's governance reform under the framework of government governance modernization. The authors bring their decades of experience in crafting policy in China to explain the relationship between China's government and market, between government and society, between the central government and local governments, functional transformation, organizational structure optimization, reform of public institutions, allocation of fiscally supported personnel, the building of a law-based government and other major issues, while also laying out a case for structural changes in the years to come. Ronghua Shen is Deputy Secretary General and research fellow at the Chinese Public Administration Society, Executive Vice-president of National Administration Science Teaching Research Society, and a specially-appointed professor and guest professor at Renmin University of China, University of International Business and Economics, Shenzhen University, China. He has worked on structural reform research at ministries under the Central Government for many years. He has published more than 20 books including Chinese Government Reform, Government Mechanism, and more than 100 papers in key publications. Sheng Cao is Deputy Secretary General of Policy Science Institute of Chinese Public Administration Society and a research fellow at the Public Administration Research Center, China. He holds a doctorate in political science from Peking University, China. He has published dozens of papers in publications such as Journal of Social Sciences and Chinese Public Administration. .